Switching treatments in haemophilia: is there a risk of inhibitor development?. (17th September 2014) - Santagostino, Elena; Auerswald, Günter; Benson, Gary; Dolan, Gerry; Jiménez‐Yuste, Victor; Lambert, Thierry; Ljung, Rolf; Morfini, Massimo; Remor, Eduardo; Zupančić Šalek, Silva
Abstract: Patients with haemophilia A (and their physicians) may be reluctant to switch factor VIII (FVIII) concentrates, often due to concerns about increasing the risk of inhibitors; this reluctance to switch may contribute to patients missing the clinical benefits provided by the arrival of new factor VIII products. This topic was explored at the Eleventh Zürich Haemophilia Forum. Clinical scenarios for which product switching may be cause for concern were discussed; when there is a clinical need, there are no absolute contraindications to switching, but some patients (e.g. previously untreated patients and those undergoing elective surgery) may require more careful consideration. Both patient and physician surveys indicate that the reluctance to switch, and the fear of inhibitor development, does not appear to be evidence based. The evaluation of more recent data did not support previous studies suggesting that particular products (e.g. recombinant vs. plasma‐derived and full length vs. B‐domain modified) may be associated with increased risk. In addition, data from three national product switches showed that switching was not associated with increased inhibitor risk, but highlighted the need for regular inhibitor testing and for a centralised, unbiased database of inhibitor incidence. To conclude, current evidence does not suggest that switching products significantly influences inhibitor development.